Preparations of Betulinic Acid Derivatives - Mohd Ali, Mohd Tajudin (2004)
Betulinic acid, 3~hydroxy-lup20(29)-ene-28-oic acid is a pentacyclic triterpene. Esterification reactions of betulinic acid were investigated. Betulinic acid esters such as 3-0-succinyl-betulinic acid, 3-0-(2',2'-dimethylsucciny1)-betulinic acid, 3-0-(3',3'-dimethylsucciny1)-betulinic acid and 3-0-glutaryl-betulinic acid were prepared. Their structures were determined by spectroscopic methods. Optimization studies on the esterification reactions were carried out for betulinic acid with succinic anhydride and with 2',2'-dimethylsuccinic acid only. The effects of varying parameters such as the mole ratio, temperature, time course and mole of catalyst were investigated. Generally, the optimal conditions for preparing 3-0-succinyl-betulinic acid was obtained by mixing betulinic acid with succinic anhydride in a 1:8 ratio and refluxing in 0.124 mole of pyridine for 24 hours at a temperature of 115°C ; the optimal conditions for the preparation of 3-0-(2',2'-dimethylsucciny1)-betulinic acid was obtained by refluxing betulinic acid and Zf,2'-dimethylsuccinic acid in a 1:6 ratio with the presence of 0.124 mole of pyridine for 24 hours at a temperature of 85°C. The percentage conversions as detected by gas chromatography analysis were 53.5 and 56.2%, respectively.